2018
DOI: 10.1113/jp274986
|View full text |Cite
|
Sign up to set email alerts
|

Layer‐specific excitation/inhibition balances during neuronal synchronization in the visual cortex

Abstract: Rhythmic activity can synchronize neural ensembles within and across cortical layers. While gamma band rhythmicity has been observed in all layers, the laminar sources and functional impacts of neuronal synchronization in the cortex remain incompletely understood. Here, layer-specific optogenetic stimulation demonstrates that populations of excitatory neurons in any cortical layer of the mouse's primary visual cortex are sufficient to powerfully entrain neuronal oscillations in the gamma band. Within each laye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 80 publications
(193 reference statements)
3
45
0
Order By: Relevance
“…Within L5 we found a heterogeneous response, where inhibition outweighed excitation in Rbp4-cre positive neurons (and possibly others which remained nonresponsive during the entire experiment) but excitation outweighed inhibition in other neurons in L5. While this paper was in review, another study interrogated the same circuit with optogenetic stimulation and simultaneous triple whole cell patch clamp, with broadly similar conclusions 35 , though the rigors of patch clamp limited the measurements to a few tens of neurons overall.…”
Section: Discussionmentioning
confidence: 75%
“…Within L5 we found a heterogeneous response, where inhibition outweighed excitation in Rbp4-cre positive neurons (and possibly others which remained nonresponsive during the entire experiment) but excitation outweighed inhibition in other neurons in L5. While this paper was in review, another study interrogated the same circuit with optogenetic stimulation and simultaneous triple whole cell patch clamp, with broadly similar conclusions 35 , though the rigors of patch clamp limited the measurements to a few tens of neurons overall.…”
Section: Discussionmentioning
confidence: 75%
“…We focused on neurons from L2/3 because our previous investigations identified them as drivers of fast oscillatory rhythms at neonatal age 13 . This layer-specificity seems to be a developmental feature of mPFC, since recent work in adult sensory cortices has shown that gamma rhythms can be driven by pyramidal neurons from all layers 15,16 . We found that light-driven fast oscillatory activity increased in power and frequency across development, similarly to what we observed for spontaneous oscillations (Fig.…”
Section: Mainmentioning
confidence: 88%
“…A slowly increasing ramp of light (peak wavelength 590 nm) was delivered via a light-emitting diode (LED) coupled to the epifluorescence port of an upright microscope, eliciting a gamma oscillation ( Fig. 1a, b), as previously reported in rodents 10,[39][40][41][42] , cats 43 and monkeys 44 . The oscillation amplitude was reduced by approximately 60% (insets), with no net change in frequency.…”
Section: Closed-loop Feedback Modulation Of Affects Gamma Oscillationmentioning
confidence: 99%
“…A slowly increasing ramp of light (peak wavelength 590 nm) was delivered via a light-emitting diode (LED) coupled to the epifluorescence port of an upright microscope, eliciting a gamma oscillation ( Fig. 1A, B), as previously reported in rodents (Adesnik, 2018;Adesnik and Scanziani, 2010;Akam et al, 2012;Butler et al, 2016;Pastoll et al, 2013), cats (Ni et al, 2016) and monkeys (Lu et al, 2015). (C) Closed-loop oscillation clamp applied between 6 and 8 s, obtained by multiplying the ramp command by (1 + k 1 LFP + k 2 dLFP/dt), with dLFP/dt averaged over 2 ms intervals.…”
Section: Closed-loop Feedback Modulation Of Affects Gamma Oscillationmentioning
confidence: 99%